Sense of Svalbard. A study of place attachment through winter recreation on Svalbard - Aamot, Dóra Bimbó (UiT The Arctic University of Norway, 2016)
Even though Svalbard has been pronounced as “no place for humans”, primarily because of its location, climate and remote appearance, it has been recognized several times in books and articles. As a consequence, tourism in the archipelago started about 100 years ago. The biggest increase in tourism occurred during the last 25 years, due to technological advances and to symbiotic co-operation between the tourism industry, researchers and governing bodies. Today, during both summer and winter, it attracts visitors from all continents. From the moment we are born, we seek safety, comfort and satisfaction. Then during the first months of our life, the longing and need for attachment begins and continues throughout our lifetimes. This emotional bond connects us with others through time and space. It can be directed not only towards humans but towards animals, objects and places as well. A physical place can appear as a special place – a place to practice and concentrate on hobbies; a place to be together with others; and a place, which reflects who we really are – a place for personal growth. The term “sense of place” describes the characteristics which make a place unique and special, and evoke belonging and attachment needs. This Master’s research was conducted in Longyearbyen using a quantitative survey to reveal and understand the interaction between place attachment and tourist experience during winter recreation in Svalbard. The research aim was to provide a holistic representation of the relationships between human and environment, and uncover factors, which can make the winter tourism of Svalbard meaningful enough to arouse positive attachment. The thesis also describes how personal experiences and physical, emotional and social aspects can affect a person’s relation to places. Keywords: place attachment, Svalbard, arctic, winter tourism, quantitative research